2012
DOI: 10.1149/ma2012-02/29/2486
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterizations on Chemical Mechanical Polishing Compositions of Polishing Ruthenium Films in CMP Processes

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In contrast, slurries preferred for interconnect applications of Co should also have very low DRs (≤1 nm/min) but with RRs that exceed 100 nm/min or so 29 while also minimizing individual corrosion as well as galvanic corrosion between Co and the underlying liner (Ti/Ta). Furthermore, it is critical to understand if the intermediate Ti/TiN or Ta/TaN layers between the Co film and Si substrate influence polishing performance as was seen with the Ru films.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, slurries preferred for interconnect applications of Co should also have very low DRs (≤1 nm/min) but with RRs that exceed 100 nm/min or so 29 while also minimizing individual corrosion as well as galvanic corrosion between Co and the underlying liner (Ti/Ta). Furthermore, it is critical to understand if the intermediate Ti/TiN or Ta/TaN layers between the Co film and Si substrate influence polishing performance as was seen with the Ru films.…”
mentioning
confidence: 99%
“…This difference is important since it was shown that the removal and static etch rate behavior of PVD and CVD Co films differ significantly from each other. 29 Recent patent literature suggests several slurry compositions with the required higher removal rates along with the necessary removal rate selectivity toward other liner/barrier layers (Ta/TaN, Ti/TiN) and dielectrics (TEOS, SiN, low-k, and ultra-low-k films). 29,[31][32][33] For example, Wang et al 31 have developed a polishing composition comprising 3 wt% abrasives, a weak acid acting as a complexing agent, at least one-azole containing corrosion inhibitor, water, and a pH adjustor as needed in the pH range of 7-12.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Typically, interconnect CMP is a two-step process. 2 The first step involves removal of the overburden at ∼300 nm/min or more 11 till about 10-20 nm of it remains. Then, a second step removes the residual Co along with the underlying liner/barrier at a relatively slower rate of ∼20-50 nm/min 12,13 while, and more importantly, controlling the galvanic corrosion between Co-Ti (liner) and Ti-TiN (barrier) couples and achieving close to 1:1:1 removal rate (RR) selectivity for Co:Ti:TiN and stopping on the low-k dielectric.…”
mentioning
confidence: 99%
“…The result shows that glycine can complex with cobalt oxide to form Co(II)-glycine complex, and improve the quality of the post-CMP Cobalt surface. Shi et al 29 used β-alanine and glycine as double chelating agents to study the polishing of cobalt at PH = 7. Optimized polishing composition can increase Cobalt removal rate to 500 nm min −1 .…”
mentioning
confidence: 99%